Epidemiology and specific humoral immunity during human Papillomavirus infection : public health implications for the prevention of associated cancers - (:unkn) unknown (My University, 2019)
High-risk human papillomavirus (HR-HPV) [groups a7 (HPV-18, -45 and -68) and a9 (HPV-16, -31, -33, -35, -52 and - 58)] are the etiological agents of cervical cancer, which is now the first female cancer in several countries in sub-Saharan Africa. Our first objective was to build research hypotheses based on literature data, by writing two extensive reviews of the literature, one on cervical cancer in Africa, and the other on systemic and genital humoral immunity specific against HPV. Our second objective was to collect biological collections from clinical cohorts of Africans at risk for oncogenic HPV infection in sub-Saharan Africa (Central African Republic, Chad) and France (1st generation immigrant women). Our third goal was to acquire and transfer sophisticated techniques of medical virology (detection and genotyping of HPV by multiplex real-time PCR) and immunology [production of "virus-like particles" (VLPs) and development a serological test for the detection of systemic and mucosal immunoglobulins G against HR-HPV groups a7/a9]. Our fourth objective was to apply the acquired molecular techniques to describe the molecular epidemiology of HPV infection in cohorts of African individuals (Chadian women, African immigrant women living in France, Central African homosexual men) and to predict within these, the efficacy of multivalent prophylactic vaccination against HPV. In these cohorts we have demonstrated: i) particularly high prevalence of oncogenic HPV infections and HIV-1 infection; (ii) atypical molecular epidemiology of oncogenic HPV infections, with an HR-HPV distribution very different from that currently observed in developed countries; and lastly, iii) a potential predictive efficacy of prophylactic vaccination with Gardasil-9® nonavalent vaccine. Finally, our fifth and last objective was to apply the acquired immunological techniques ("VLP-based ELISA") to evaluate the immune response to systemic and mucosal IgG against HR-HPV of the a7/
Keywords: African Research